Антропотехніки філософії М. Фуко (суперечливий характер інтерпретації терміну тілесності) - Бораковська, М. О. (НТУ "ХПІ", 2017)
У статті досліджується суперечливий характер інтерпретації терміну тілесності, відбувається спроба розробити методологічну стратегію аналізу людської тілесності, спираючись на філософський метод М. Фуко. За допомогою техніки гуманітарного пізнання розкривається змістовне наповнення понять дискурс, епістема, дискурс тілесності, біовлада. Запропоновано дослідження тілесності, орієнтуючись на антропологію практик влади, які конструюють людську тілесність.

The article examines the contradictory interpretations of physicality, there is an attempt to develop a methodological strategy for the analysis of human embodiment, based on the philosophical method of Michel Foucault. The content of the concepts of discourse, episteme, the discourse of corporeality, biopower are revealed using the technique of human cognition. It is proposed the study of corporeality, focusing on the anthropology of the practices of power that construct human physicality.
Anthropotechnique philosophy of Michel Foucault (contradictory interpretation of the term corporeality)
Keywords: тілесність; біовлада; дискурс тілесност; епістема; структуралізм; corporality; biopower; discourse of corporeality; episteme; structuralism